Proceso de atención de enfermería en neonato con síndrome de dificultad respiratorio. - Nivela Jiménez, Silvia Katiuska (2022)
Nursing process of a male newborn of 36.1 weeks of gestation diagnosed with respiratory distress syndrome, which is one of the most common medical conditions in newborns. The purpose of this process is to relieve and rehabilitate patients by identifying changing needs, applying knowledge and procedures to improve their health. The methodology used was directed to the study of the pathological causes, clinical picture, treatment and diagnosis, using various methods of data collection as a condition, development of a care plan according to the main needs of the newborn, and it has been found that the care interest have been made with the aim of improving the condition of the newborn. Thus, as can be seen in the details of this case study, it was possible to state in its entirety where the favorable evolution of the patient improved the objectives set thanks to the processes carried out.